POLEMIK HUBUNGAN KELUARGA DALAM SENGKETA WARIS: STUDI KASUS GUGATAN DI YOGYAKARTA PUTUSAN NOMOR 72/Pdt.G/2022/PNYyk - Anabella Andini; Ghaniya Raisa Watanata; Irene Marcella; Imanuel Faano Zega; Josephine Milhan Tan; Vionita Cicilia; Yuni Priskila Ginting (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2024)
Family relations play a significant role in inheritance distribution, as regulated under Indonesia’s Civil Code (KUHPerdata) and Marriage Law. This study aims to analyze the polemics of inheritance disputes within a family in Yogyakarta, as addressed in Decision Number 72/Pdt.G/2022/PN Yyk. Using normative legal research methods with a doctrinal approach focused on secondary data, the findings highlight the importance of establishing family relationships through documents such as birth certificates, marriage certificates, and family cards to determine the rights and obligations of heirs. The distribution of inheritance is carried out according to the legal hierarchy of heirs as stipulated in the Civil Code. This study is expected to deepen understanding of family relationship verification in inheritance disputes and contribute to legal policy reforms regarding inheritance in Indonesia.